Exploring the use of the perceived stress scale for children as an instrument for measuring stress among children and adolescents: a scoping review - Kornienko, Dmitry S.; Rudnova, Natalia A.; Veraksa, Aleksander N.; Gavrilova, Margarita N.; Plotnikova, Valeria A. (Frontiers in Psychology, 2024)
This review examines the application and findings related to the Perceived Stress Scale for Children (PSS-C) since its development by B. White in 2014. The PSS-C is designed to assess children's perceived stress, focusing on their subjective experience rather than objective stressors. Our review utilized the PRISMA method to systematically collect and analyze pertinent literature, with a specific focus on studies which utilized the PSS-C. A comprehensive screening process reduced the extensive initial search results from various databases, ultimately resulting in the inclusion of 21 studies. These studies were assessed based on criteria that included publication date, language, and relevance to children's perceived stress.We categorized the selected studies into several themes: 1) the impact of COVID-19 and the return to school; 2) mindfulness as a coping mechanism; 3) the effectiveness of breathing techniques; 4) mental health intervention programs; and 5) the cultural context of stress.The review also highlighted potential biases in the studies, particularly concerning sample size and randomization procedures. Key findings from the reviewed studies included the significant impact of the COVID-19 pandemic on children's perceived stress, the role of mindfulness and breathing techniques in stress reduction, and the effectiveness of intervention programs.In conclusion, the review emphasized the significance of the PSS-C as a tool for evaluating perceived stress in children and stressed the necessity for additional research to examine its connections with different psychological and social factors. The findings underscore the importance of supportive parent-child interactions, especially during challenging situations such as the COVID-19 pandemic, and the possible advantages of mindfulness and other coping mechanisms in reducing stress. Subsequent research should persist in enhancing stress assessment tools and exploring the enduring impacts of stress on children's growth and welfare.